Proposta de um modelo de gestão que faça o controle estratégico da manutenção preventiva aplicado a perfuratrizes - SANTOS, Rodrigo Ribeiro (2019)
With the intention of becoming more and more competitive, increasing production, reducing costs, and improving the quality of its products, organizations have, over the last decades, improved their maintenance processes by adding philosophies, methodologies, control systems and tools monitoring, all to ensure greater maintainability and avoid failures. Over the years, maintenance management has evolved and required the efforts, attitudes and skills of managers and staff in their control and in taking strategic actions. Thus, one of the maintenance monitoring and evaluation tools is the Performance Indicators. Among the main ones we can mention: Disponibility (DF), Mean Time Between Failures (MTBF) and Mean Time To Repair (MTTR). The indicators give us important informations regarding the quality of the maintenance performed. Controlling and improving them ensures greater availability and reliability of equipments. The present work sought to create a control system that allows to evaluate in detail the problems of performance and occurrences of failures, in order to assure greater assertiveness in the strategic decision making, focusing efforts on key points of recurrent problems. With the applied methodology and having generated actions, the results achieved confirmed the feasibility of the method so that it could be applied to the other machines of the supervision of preventive maintenance of drillings of a mining company in the state of Pará where the highest results reached a gain of 11.23% in DF, 110.97% of MTBF, and a decrease of 65.56% in MTTR.